(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
We can define as ethics to the part of the philosophy constituted by a set of norms that are present and direct human behavior. In the concept of integral training that professionals should receive during higher education, ethics constitutes the cornerstone in which no commitment, clarity of ethical concepts and a high level of personal and social responsibility should not miss. Establish ethical foundations in the practice of health professionals in order to provide a support tool in decision -making before ethical dilemmas, analyze ethics in the health field and know the role of ethics in the training of Health professionals. Every professional should know that their service dimension must always be to see academic and technical competences.